Exploring grammatical development in children aged 2;6 to 7: a novel approach using elicited production. - Kauschke, Christina; Lawatsch, Kim; Tenhagen, Anne; Dörfler, Tobias (Clinical Linguistics & Phonetics)
The assessment of children's grammatical skills is a crucial component of diagnosing language disorders. Elicited production is a commonly used method for obtaining data on a child's productive language abilities. We introduce a new instrument developed as part of the third edition of a standardised test battery for German. This instrument utilises elicited production, wherein participants describe coloured pictures depicting everyday situations, in order to generate four test scores: mean length of utterances, completeness of utterances, and two grammar scores comprising relevant target structures. The construction of the grammar scores was inspired by the Index of Productive Syntax (IPSyn), modified for German and computerised. The detailed results provide a comprehensive profile of a child's syntactic and morphological strengths and weaknesses. Analysis of data collected from 348 monolingual German children who formed part of the norming sample, aged between 2;6 and 6;11 years of age, revealed age-related changes in these scores. Additionally, the age range was determined for both grammatical milestones and 'red flags', which may indicate potential problems in language development. In conclusion, the newly developed, time-efficient instrument allows for a detailed assessment of grammatical skills, identification of potential intervention targets, and facilitates various research objectives.